Ensuring the Sustainability of Local Broadcasting through Citizen Engagement - Hitoshi Mitomo; Tokio Otsuka (International Telecommunications Society (ITS), 2024)
This study aims to investigate the feasibility of sustaining local terrestrial broadcasting in rural Japan through citizen engagement. Commercial broadcasters in Japan have been sustained by advertising revenue. However, due to the proliferation of rich Internet content, much of the advertising expenditure of sponsor companies has shifted to the Internet. Thus, many local broadcasters in Japan have faced financial difficulties due to decreased commercial revenue. To maintain broadcasting, diverse sources of revenue must be secured, and one way to achieve this is to support local broadcasting that is closely connected to their communities through local residents' engagement. This paper examines the possibility of citizen engagement. It quantitatively analyzes whether they are willing to provide financial support as an engagement and how much they are willing to pay based on a hypothetical scenario. A contingent valuation method (CVM) is applied to estimate the willingness-to-pay (WTP) for local television (TV) programs and broadcasters.
Keywords: 330